2017
DOI: 10.1159/000485862
|View full text |Cite
|
Sign up to set email alerts
|

Association Between GLCCI1 Promoter Polymorphism (Rs37972) and Post-Transplant Hypertension in Renal Transplant Recipients

Abstract: Background/Aims: Post-transplant hypertension is highly prevalent in renal transplant recipients and is a risk factor for graft loss, cardiovascular disease and death. Glucocorticoid is used to prevent rejection, but simultaneously increases the risk of post-transplant hypertension. The glucocorticoid-induced transcript 1 (GLCCI1) promoter polymorphism (rs37972) has been reported to be associated with response to glucocorticoid therapy in asthma. We therefore examined the association between GLCCI1 promoter po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…A previous study demonstrated that IGFBP5 , 223 PRDX6 , 224 PKM (pyruvate kinase M1/2) , 225 PRDX1 , 226 and USP22 227 were more highly expressed in diabetic nephropathy. Durgin et al, 228 Zhang et al, 229 Hamada et al, 230 Gong et al, 231 Li et al, 232 Lin et al, 233 and Schweigert et al 234 suggested that CYB5R3, CACNA1A, GLCCI1, CAP1, HSP90AB1, BLVRA (biliverdinreductase A), and CRIP1 were involved in the progression of hypertension. These results suggested that these, cognitive impairment, cardiovascular diseases, obesity, diabetic nephropathy and hypertension responsible genes might influence the development of T2DM through the altered expression.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that IGFBP5 , 223 PRDX6 , 224 PKM (pyruvate kinase M1/2) , 225 PRDX1 , 226 and USP22 227 were more highly expressed in diabetic nephropathy. Durgin et al, 228 Zhang et al, 229 Hamada et al, 230 Gong et al, 231 Li et al, 232 Lin et al, 233 and Schweigert et al 234 suggested that CYB5R3, CACNA1A, GLCCI1, CAP1, HSP90AB1, BLVRA (biliverdinreductase A), and CRIP1 were involved in the progression of hypertension. These results suggested that these, cognitive impairment, cardiovascular diseases, obesity, diabetic nephropathy and hypertension responsible genes might influence the development of T2DM through the altered expression.…”
Section: Discussionmentioning
confidence: 99%